ANALISIS KINERJA PERAWAT SAAT MASA WABAH COVID-19 DI RUMAH SAKIT BHAYANGKARA PEKANBARU TAHUN 2020 - Dedy Prasetyo Hadi; Budi Hartono; Yulfitriana Amir (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
WHO has designated Covid-19 as a case of a global pandemic that has infected millions of people, whose numbers have continued to increase from time to time. The burden on hospitals is getting higher in handling Covid-19 patients, In connection with this, the existence of hospitals and medical personnel is needed as the front line in dealing with this pandemic. The purpose of this study is to analyze the performance of nurses during the Covid-19 outbreak at Bhayangkara Hospital Pekanbaru in 2020. This type of research is quantitative descriptive observational with cross sectional design. The population of all nurses at Bhayangkara Hospital Pekanbaru is 51 people. The sampling technique was total sampling. Primary data collection was carried out by distributing questionnaires online. Data analysis was carried out by univariate, bivariate and multivariate multiple logistic regression. The results showed a bivariate analysis of variables that had a significant relationship with the nurse's performance, namely knowledge OR = 1.364, workload OR = 2.714, work stress OR = 2.200, motivation OR = 1.617, incentive OR = 17.14, work environment OR = 4.541. Based on multivariate analysis, work stress and motivation variables are more dominant in the performance of nurses. The conclusion of this study is that there is a significant relationship between job stress and motivation on the performance of nurses during the Covid-19 outbreak at Bhayangkara Hospital Pekanbaru.